Resilience: A New Paradigm for Adaptation to Chronic Pain - Sturgeon, John A. (Curr Pain Headache Rep, 2010)
Chronic pain is an affliction that affects a large proportion of the general population and is often accompanied by a myriad of negative emotional, cognitive, and physical effects. However, current pain adaptation paradigms do not account for the many chronic pain patients who demonstrate little or no noticeable impairment due to the effects of chronic pain. This paper offers resilience as an integrative perspective that can illuminate the traits and mechanisms underlying the sustainability of a good life and recovery from distress for individuals with chronic pain.